Horor Coronavirus Diseases dan Konflik Kekerasan Masyarakat: Tinjaun Sosiologis atas Penolakan Jenazah Pasien Covid-19 - Mahyuddin Mahyuddin; Ilham Ilham; Muhammad Rusdi (Jurnal Commercium: Kajian Masyarakat Kontemporer, 2020)
This study aims to determine the causes of violent conflict in the community during the pandemic. The description of this article outlines a sociological theoretical explanation of the phenomenon of public rejection of the bodies of Covid-19 patients in various locations. This research used a qualitative paradigm with a case study approach. The phenomenon was analyzed using the theory of hyperreality by Jean-baudrillard and the anomie theory of Emile Durkheim's approach. The analysis of these two sociologists led the writer to investigate the causes of the social problems and see the social impacts that covered them. The results of the study revealed that the occurrence of violent conflict in the early days of the pandemic was caused by the hyperreality of the community. Covid-19's transition period that was full of flaming, had an impact on the social system and social structure. It have given the consequences in the form of deviant actions in society.